Optimasi Penjadwalan Produksi Sanjai Rina Menggunakan Algoritma Campbell Dudek Smith - annisa yovinda; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2022)
Abstract — Kerupuk sanjai Rina business always run into lateness in product delivery because they haven’t done production which will be deliver and delivery deadline only based on intuition. Sanjai Rina have need to establist a better production schedule so that be able to minimizing all product work time total. There are many ways to minimizing total of work time, one of them is using Campbell Dudek Smith (CDS) algorithm. The purpose of the research to know best outcome sanjai Rina production prosess scheduling using CDS algorithm. CDS algorithm obtain k iteration with different values. From k iteration, minimal value will be use to determine production thread. Sanjai Rina business have total time work all of product is 435,88 hours by sequence 1-2-3-4-5-6-7-8. From CDS algorithm iterations, obtain minimal scheduling by sequence 4-8-3-1-2-6-7-5 with total work time all of yhe product is 375,26 hours that will attain saving 60,22 hours time work.